2022
DOI: 10.1016/j.jcmgh.2021.11.007
|View full text |Cite
|
Sign up to set email alerts
|

TM6SF2/PNPLA3/MBOAT7 Loss-of-Function Genetic Variants Impact on NAFLD Development and Progression Both in Patients and in In Vitro Models

Abstract: The co-presence of I148M PNPLA3 Q11 , the rs641738 close to MBOAT7, and the E167K TM6SF2 at-risk variants impacts the course of nonalcoholic fatty liver disease in both patients and experimental models. They affect lipid droplet accumulation, mitochondrial functionality, and metabolic reprogramming, leading to hepatocarcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 52 publications
1
51
0
Order By: Relevance
“…In the future, comprehensive analysis including anti-HBc, hepatitis B surface antibody, and HBV DNA status is required to clarify the role of OBI in these special populations. Finally, the gene polymorphisms including TM6SF2/PNPLA3/MBOAT7 which are highly related to the abnormal metabolic disease and fatty liver disease are not evaluated in our study ( 57 , 58 ). Futher studies are needed to investigated whether the proportion of SNPs in NBNC-HCC is getting higher.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, comprehensive analysis including anti-HBc, hepatitis B surface antibody, and HBV DNA status is required to clarify the role of OBI in these special populations. Finally, the gene polymorphisms including TM6SF2/PNPLA3/MBOAT7 which are highly related to the abnormal metabolic disease and fatty liver disease are not evaluated in our study ( 57 , 58 ). Futher studies are needed to investigated whether the proportion of SNPs in NBNC-HCC is getting higher.…”
Section: Discussionmentioning
confidence: 99%
“…The first procedure consists of editing the genetic defect by exploiting different technologies such as zinc finger nucleases, CRISPR-Cas9, and engineered, replicationincompetent viral vectors [88][89][90]. Among them, DNA transfer vectors derived from recombinant adeno-associated viruses (rAAV) have been successfully applied in the treatment of inherited disorders and, in recent years, they have been optimized to ensure the long-term expression of a specific protein, to ensure safety and tissue tropism, and to avoid immunogenicity [90][91][92].…”
Section: Gene Therapy Mrna-based Therapies and Apolipoprotein For Pro...mentioning
confidence: 99%
“…Meanwhile, the I148M point mutation in the patatin-like phospholipase domain-containing protein 3 (PNPLA3) gene represents one of the most significant predisposing factors to NAFLD development and advanced liver damage, indicating that there is also a genomic background in NAFLD pathogenesis [ 82 , 83 , 84 , 85 ]. In fact, it has been suggested that the accumulation of PNPLA3-148M on the surfaces of lipid droplets (LDs) inhibits triacylglycerol hydrolysis and leads to the impaired mobilization of triglycerides from LDs [ 86 , 87 , 88 ].…”
Section: Overview Of Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%